INTEGRASI TEKNOLOGI AI DALAM PROSEDUR PEMBUATAN AKTA OTENTIK: TANTANGAN DAN PELUANG DALAM SISTEM HUKUM INDONESIA - Andi Suriangka; Amalia Hamzah; Muhd. Alif Fathan (LPPM STIH Awang Long, 2026)
The integration of Artificial Intelligence (AI) into notarial work is no longer a distant possibility, but an emerging issue in Indonesia’s legal services. This article examines how AI can be used in the procedure of drafting authentic deeds without weakening the essential character of authenticity, legal certainty, and the public trust attached to the notarial office. The study applies a normative legal method through statutory, conceptual, and limited comparative approaches. Primary legal materials include the Civil Code, the Notary Law, the Electronic Information and Transactions Law, the Personal Data Protection Law, and regulations on electronic systems. Secondary materials include recent literature on cyber notary, legal technology, AI governance, and comparative AI regulatory models. The findings show that AI may support notaries in preliminary drafting, document consistency checking, archive management, risk detection, and preparation of administrative checklists. However, AI cannot replace the notary’s authority to verify the parties’ will, read the deed, assess legal capacity, ensure formal requirements, and assume personal responsibility for the deed. The absence of sector-specific rules on AI in notarial practice creates legal uncertainty concerning authenticity, liability, confidentiality, and data protection. This article proposes an AI-assisted authentic deed model based on human-in-command, limited delegation, auditability, data protection by design, and system certification. Proper regulation is needed so that AI strengthens, rather than erodes, the evidentiary value and social legitimacy of authentic deeds in Indonesia.